Can Microbiome Modulate Regenerative Capacity? A Comparative Microbiome Study Reveals a Dominant Presence of Flavobacteriaceae in Blastema Tissue During Axolotl Limb Regeneration - Demircan, Turan; Gul, Sultan; Tasci, Ebru Altuntas (MARY ANN LIEBERT, INC, 2024)
The axolotl (Ambystoma mexicanum) is renowned for its remarkable regenerative capabilities, which are not diminished by the transition from a neotenic to a metamorphic state. This study explored the microbiome dynamics in axolotl limb regeneration by examining the microbial communities present in neotenic and metamorphic axolotls at two critical stages of limb regeneration: pre-amputation and during blastema formation. Utilizing 16S rRNA amplicon sequencing, we investigated the variations in microbiome profiles associated with different developmental and regenerative states. Our findings reveal a distinct separation in the microbiome profiles of neotenic and metamorphic samples, with a clear demarcation in microbial composition at both the phylum and genus levels. In neotenic 0DPA samples, Proteobacteria and Firmicutes were the most abundant, whereas in neotenic 7DPA samples, Proteobacteria and Bacteroidetes dominated. Conversely, metamorphic samples displayed a higher abundance of Firmicutes and Bacteroidetes at 0DPA and Proteobacteria and Firmicutes at 7DPA. Alpha and beta diversity analyses, along with dendrogram construction, demonstrated significant variations within and between the sample groups, suggesting a strong influence of both developmental stage and regenerative state on the microbiome. Notably, Flavobacterium and Undibacterium emerged as distinctive microbial entities in neotenic 7DPA samples, highlighting potential key players in the microbial ecology of regeneration. These findings suggest that the axolotl's microbiome is dynamically responsive to blastema formation, and they underscore the potential influence of microbial communities on the regeneration process. This study lays the groundwork for future research into the mechanisms by which the microbiome may modulate regenerative capacity.
Keywords: regenerative medicine; axolotl; microbiome; Flavobacteriaceae; metamorphosis; animal models; OXALATE-DEGRADING BACTERIA; INDUCED METAMORPHOSIS; IMMUNE-SYSTEM; MODEL; GUT; Biotechnology & Applied Microbiology; Genetics & Heredity